Interpersonal Trauma as a Marker of Risk for Urinary Tract Dysfunction in Midlife and Older Women. Issue 1 (January 2020) - Boyd, Brittni A. J.; Gibson, Carolyn J.; Van Den Eeden, Stephen K.; McCaw, Brigid; Subak, Leslee L.; Thom, David; Huang, Alison J.
Abstract : OBJECTIVE: To examine relationships between interpersonal trauma exposures and urinary symptoms in community-dwelling midlife and older women. METHODS: We analyzed cross-sectional data from a multiethnic cohort of women aged 40–80 years enrolled in an integrated health care system in California. Lifetime history of intimate partner violence (IPV) and sexual assault, current posttraumatic stress disorder (PTSD) symptoms, and current urinary symptoms were assessed using structured-item questionnaires. Multivariable-adjusted logistic regression models examined associations between traumatic exposures and PTSD symptoms with any weekly urinary incontinence, stress-type incontinence, urgency-type incontinence, and nocturia two or more times per night. RESULTS: Of the 1, 999 participants analyzed, 21.7% women reported lifetime emotional IPV, 16.2% physical IPV, 19.7% sexual assault, and 22.6% reported clinically significant PTSD symptoms. Overall, 45% reported any weekly incontinence, 23% stress-type incontinence, 23% urgency-type incontinence, and 35% nocturia. Exposure to emotional IPV was associated with any weekly incontinence (odds ratio [OR] 1.33, 95% CI 1.04–1.70), stress-type incontinence (OR 1.30, 95% CI 1.00–1.65), urgency-type incontinence (OR 1.30, 95% CI 1.00–1.70), and nocturia (OR 1.73, 95% CI 1.36–2.19). Physical IPV exposure was associated with nocturia (OR 1.35, 95% CI 1.04–1.77), but not incontinence. Sexual assault history was not associated with weekly incontinence of any type or nocturia. Symptoms of PTSD were associated with all urinary symptoms assessed, including any weekly incontinence (OR 1.46, 95% CI 1.15–1.85), stress-type incontinence (OR 1.70, 95% CI 1.32–2.20), urgency-type incontinence (OR 1.60, 95% CI 1.24–2.06), and nocturia (OR 1.95, 95% CI 1.55–2.45). CONCLUSION: More than 20% of women in this multiethnic, community-based cohort reported a history of IPV, PTSD symptoms, or both, which were associated with symptomatic urinary tract dysfunction. Findings highlight the need to provide trauma-informed care of midlife and older women presenting with urinary symptoms. Abstract : Midlife and older women with a history of interpersonal trauma are more likely to experience symptomatic urinary tract dysfunction.